Field and magic angle spinning frequency dependence of proton resonances in rotating solids - Xue, Kai; Sarkar, Riddhiman; Tošner, Zdeněk; Reif, Bernd (Progress in nuclear magnetic resonance spectroscopy, 2022)
Proton detection in solid state NMR is continuously developing and allows one to gain new insights in structural biology. Overall, this progress is a result of the synergy between hardware development, new NMR methodology and new isotope labeling strategies, to name a few factors. Even though current developments are rapid, it is worthwhile to summarize what can currently be achieved employing proton detection in biological solids. We illustrate this by analysing the signal-to-noise ratio (SNR) for spectra obtained for a microcrystalline α-spectrin SH3 domain protein sample by (i) employing different degrees of chemical dilution to replace protons by incorporating deuterons in different sites, by (ii) variation of the magic angle spinning (MAS) frequencies between 20 and 110 kHz, and by (iii) variation of the static magnetic field B0. The experimental SNR values are validated with numerical simulations employing up to 9 proton spins. Although in reality a protein would contain far more than 9 protons, in a deuterated environment this is a sufficient number to achieve satisfactory simulations consistent with the experimental data. The key results of this analysis are (i) with current hardware, deuteration is still necessary to record spectra of optimum quality; (ii) 13CH3 isotopomers for methyl groups yield the best SNR when MAS frequencies above 100 kHz are available; and (iii) sensitivity increases with a factor beyond B0 3/2 with the static magnetic field due to a transition of proton-proton dipolar interactions from a strong to a weak coupling limit.
Keywords: src homologní domény; deuterium; src Homology Domains; Proton detection; Proton Therapy; Biological solids; Protons; Spectrin; protonová terapie; Deuterium; Magic angle spinning; Solid state NMR; spektrin; protony